Adjuvant paclitaxel and trastuzumab for node-negative, HER2-positive breast cancer: final 10-year analysis of the open-label, single-arm, phase 2 APT trial. Issue 3 (March 2023) - Tolaney, Sara M; Tarantino, Paolo; Graham, Noah; Tayob, Nabihah; Parè, Laia; Villacampa, Guillermo; Dang, Chau T; Yardley, Denise A; Moy, Beverly; Marcom, P Kelly; Albain, Kathy S; Rugo, Hope S; et al.
Summary: Background: We aimed to report on long-term outcomes of patients with small, node-negative, HER2-positive breast cancer treated with adjuvant paclitaxel and trastuzumab and to establish potential biomarkers to predict prognosis. Methods: In this open-label, single-arm, phase 2 study, patients aged 18 years or older, with small (≤3 cm), node-negative, HER2-positive breast cancer, and an Eastern Cooperative Oncology Group performance status of 0–1, were recruited from 16 institutions in 13 cities in the USA. Eligible patients were given intravenous paclitaxel (80 mg/m 2 ) with intravenous trastuzumab (loading dose of 4 mg/kg, subsequent doses 2 mg/kg) weekly for 12 weeks, followed by trastuzumab (weekly at 2 mg/kg or once every 3 weeks at 6 mg/kg) for 40 weeks to complete a full year of trastuzumab. The primary endpoint was 3-year invasive disease-free survival. Here, we report 10-year survival outcomes, assessed in all participants who received protocol-defined treatment, with exploratory analyses using the HER2DX genomic tool. This study is registered on ClinicalTrials.gov, NCT00542451, and is closed to accrual. Findings: Between Oct 29, 2007, and Sept 3, 2010, 410 patients were enrolled and 406 were given adjuvant paclitaxel and trastuzumab and included in the analysis. Mean age at enrolment was 55 years (SD 10·5), 405 (99·8%) of 406 patients were female and one (0·2%) was male, 350 (86·2%) were White, 28 (6·9%) were Black or African American, and 272 (67·0%) had hormone receptor-positive disease. After a median follow-up of 10·8 years (IQR 7·1–11·4), among 406 patients included in the analysis population, we observed 31 invasive disease-free survival events, of which six (19·4%) were locoregional ipsilateral recurrences, nine (29·0%) were new contralateral breast cancers, six (19·4%) were distant recurrences, and ten (32·3%) were all-cause deaths. 10-year invasive disease-free survival was 91·3% (95% CI 88·3–94·4), 10-year recurrence-free interval was 96·3% (95% CI 94·3–98·3), 10-year overall survival was 94·3% (95% CI 91·8–96·8), and 10-year breast cancer-specific survival was 98·8% (95% CI 97·6–100). HER2DX risk score as a continuous variable was significantly associated with invasive disease-free survival (hazard ratio [HR] per 10-unit increment 1·24 [95% CI 1·00–1·52]; p=0·047) and recurrence-free interval (1·45 [1·09–1·93]; p=0·011). Interpretation: Adjuvant paclitaxel and trastuzumab is a reasonable treatment standard for patients with small, node-negative, HER2-positive breast cancer. The HER2DX genomic tool might help to refine the prognosis for this population. Funding: Genentech.